أهمیة تطبیق بطاقة الأداء المتوازن المستدام ) (SBSCفي المؤسسات الاقتصادیة. دراسة حالة مؤسسة "ملبنة التل" بسطیف - د.عریوة , محاد (Finance and Business Economies Review, 2018)
The obligation of Small and medium enterprises to sustainable development requires a combination of performance and responsibility. Financial performance is not possible to occur without performance within company. Thus Small and medium enterprises must measure its progress through the performance of a more comprehensive and balance which includes the dimensions of sustainability and this can happen only by using the tools of modern management accounting of the balanced scorecard sustainable following the merger of sustainability indicators in order to measure the dimensions of performance and evaluation of sustainability.